Literatur Review: Mengapa Rekam Medis Tidak Lengkap? - Sri Sugiarsi; Rohmadi Rohmadi (Lembaga Penerbitan Universitas Esa Unggul, 2020)
AbstractMedical records are a source of important medical data and information to present a patient's medical history and status, therefore medical records must be complete. However, incomplete medical records were still found. The purpose of this study was to find the causes of incomplete medical records. This study uses a literature review approach with the PICO framework. Literature search using the Google Scholar database. The keywords and Boolean operators used in this study are